Interaction Spaces and Socioenactive Dimensions: Exploring Perturbations of IoHT - da Silva, José Valderlei; Baranauskas, Maria Cecília Calani (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Perception and action on physical or virtual objects are related to the perturbations (light, sound, etc.) caused by them. For the design of collective spaces, with computational technologies embedded in things, it is necessary to understand the environment as a system in the Social, Physical and Digital dimensions. They exchange infor mation and perceive perturbations, acting on feedback. This vision has contributed to the conception of collective spaces in which the dimensions articulate dynamically in a Socioenative way, with a focus on human relations. The practices of Socially Aware Design (SAwD) is a way of thinking and designing Socionative systems, integrating collective actions and perceptions, between people and computing in spaces where things are organized to create an environment. In this article we present the con guration of a Physical space devel oped in a hospital to provide a Socioenative environment that has contributed to the construction and theoretical-practical evolution in the studies of socioenation. The design of artifacts to compose en vironments in the hospital helped to understand the dimensions for application in IoHT (Internet of Human Things) systems as Socioenative Systems from the perspective of SAwD, and to map the dimensions in relation to their composition, characteristics, dynamics and interdependencies, allowing the visualization of their connections.